2018
DOI: 10.3390/rs10091326
|View full text |Cite
|
Sign up to set email alerts
|

How Long should the MISR Record Be when Evaluating Aerosol Optical Depth Climatology in Climate Models?

Abstract: This study used the nearly continuous 17-year observation record from the Multi- angle Imaging SpectroRadiometer (MISR) instrument on the National Aeronautics and Space Administration (NASA) Terra Earth Observing System satellite to determine which temporal subsets are long enough to define statistically stable speciated aerosol optical depth (AOD) climatologies (i.e., AOD by particle types) for purposes of climate model evaluation. A random subsampling of seasonally averaged total and speciated AOD retrievals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…They found that in and downwind of some strong aerosol source regions (including the biomass burning sampled at Alta Floresta), upward of a decade could be required. Although spatial patterns were similar between their MODIS and MISR results, Lee et al () found that MODIS‐based estimates of needed record length were often 1–3 years higher than those from MISR, perhaps due to differences in treatment and sampling of high‐AOD events between these data sets. Further study on this topic would be worthwhile for the future.…”
Section: Intercomparisons Of Aod Time Series Between Modis Viirs Anmentioning
confidence: 84%
See 1 more Smart Citation
“…They found that in and downwind of some strong aerosol source regions (including the biomass burning sampled at Alta Floresta), upward of a decade could be required. Although spatial patterns were similar between their MODIS and MISR results, Lee et al () found that MODIS‐based estimates of needed record length were often 1–3 years higher than those from MISR, perhaps due to differences in treatment and sampling of high‐AOD events between these data sets. Further study on this topic would be worthwhile for the future.…”
Section: Intercomparisons Of Aod Time Series Between Modis Viirs Anmentioning
confidence: 84%
“…An implication of this is that climatologies of AOD generated from satellite products in these regions may be sensitive to exactly which years are used to generate the climatology. Recently, Lee et al () attempted to quantify the role of interannual variability by assessing the record length needed to obtain a stable (to within 0.01) annual or seasonal mean AOD field from Multiangle Imaging Spectroradiometer (MISR) or MODIS data. They found that in and downwind of some strong aerosol source regions (including the biomass burning sampled at Alta Floresta), upward of a decade could be required.…”
Section: Intercomparisons Of Aod Time Series Between Modis Viirs Anmentioning
confidence: 99%
“…This does mean that interannual variations could influence the composites for these two sensors. However, recently, Lee et al () used MODIS and MISR data to evaluate how many years were required to define a climatology of AOD within a sampling uncertainty (relative to full mission) of less than 0.01. They found that over the bulk of the open ocean, 2 years appeared sufficient, while in coastal outflow regions (e.g., dust/smoke belts) the time period was more often 4–12 years, dependent on region and distance from aerosol source.…”
Section: Comparison To Other Over‐water Satellite Data Setsmentioning
confidence: 99%
“…To assess their consistency, the products should be compared during overlapping periods, because interannual and shorterterm variability can be significant in some parts of the world (e.g. Lee et al 2018). In the current study, AOD monthly aggregates from different products were evaluated with ground-based measurements such as those from the Aerosol Robotic Network (AERONET, Holben et al, 1998).…”
Section: Introductionmentioning
confidence: 99%